Implementation of Ibadah-Friendly Hospital Care: The Challenges - Isma’il, Salisu (International Journal of Human and Health Sciences (IJHHS), 2024)
Ibadah-friendly Hospital (IFH) practice enables patients, patient’s relatives and Muslim health workers to observe their religious obligations properly, especially five daily prayers while on hospital admission and duty respectively. The concept is backed by the Qur'an 51, verse 56 whereAllah said “I have not created 'jin' and 'ins' except to worship Me”. Muslims are generally conscious about observing Salat when it is time, and anywhere they are, however this consciousness is not directly translated to the situations in the hospitals. It is observed that the majority of hospitalized patients were not consistently observing their five daily prayers, this prompted Muslim health workers to embark on the campaigns for understanding and implementing IFH care. Even though the concept of IFH care is not new to Muslim Ummah, its implementation is slowed by so many challenges ranging from inadequate religious knowledge, misunderstanding of the concept, lack of commitment by the hospital administrators as well as Western orientation of medical practice to mention a few, hence there is need for continuous and sustained awareness campaigns to improve the acceptance as well as the practice of IFH care worldwide. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S25